PERUBAHAN MORFOLOGI KATUP MITRAL PADA DEMAM REMATIK AKUT DAN PENYAKIT JANTUNG REMATIK - Dede Jumatri Tito; Mefri Yanni (Universitas Fort De Kock, 2020)
Rheumatic fever and rheumatic heart disease remains a significant cause of cardiovascular disease in the world, especially in industrial countries and developing countries. Rheumatic heart disease is the most serious complication of rheumatic fever which is characterized by the occurrence of heart valve defects are most of the mitral valve, aortic and tricuspid followed. Valvulitis or inflammatory process in the tissue of the mitral valve causing edema of the valve leaflets and chordae tendineae, causing disruption valve closure is causing mitral regurgitation. Eventually fibrosis and calcification of the valve that causes stiffness and the valve leaflets into mitral valve stenosis. The earliest possible introduction of cardiac involvement in rheumatic heart disease is an important part in the prevention of further heart damage.